PARTISIPASI MASYARAKAT DAN PERAN PENDAMPING DALAM PEMBERDAYAAN KELOMPOK USAHA BERSAMA (KUBE) MELATI 3 DI KELURAHAN GALUR - Nazera Nur Utami; Sari Viciawati Machdum (Indonesian Journal of Social Work, 2021)
The social problem faced by the community is poverty which causes inequality in community groups. The government has conducted community empowerment in the joint business group program to improve the standard of living of the poor. One of them is KUBE Melati 3 which is located in Johar District, Galur Village, Central Jakarta. The results showed that the participation of KUBE members and the role of companion. Member participation is described in the involvement of realizing group business skills, the hope of building groups, decision making collaboration, contributing ideas through deliberation, managing supplementary feeding, competitions, and financial contributions. And the companion roles is facilitative, educational, representative, and technical role in empowerment efforts. This research was conducted using a qualitative approach with descriptive research type. In-depth interviews were conducted with 10 informants who were selected through purposive sampling technique.